4. SURVEY OF ANEMIA RATES AND RELATED FACTORS IN PREGNANT WOMEN UNDERGOING TESTING AT HANHPHUCLAB IN 2024 (Vietnam Journal of Community Medicine, 2024)
Objective: To determine the prevalence of anemia, bone marrow response through reticulocyte count, and factors influencing these among pregnant women undergoing testing at HANHPHUCLAB Medical Diagnostic Center in 2024.Method: A cross-sectional descriptive study was conducted on 180 pregnant women at HANHPHUCLAB from March to May 2024. Blood samples were collected from the pregnant women for Hb and reticulocyte count testing.Results: 180 pregnant women met the study criteria, with an anemia prevalence of 11.7% and predominantly microcytic hypochromic anemia at 23.8%. Among pregnant women, 9.5% of anemic pregnant women and 11.3% of non-anemic pregnant women showed increased reticulocyte counts. The study found a statistically significant association between anemia and gestational weeks.Conclusion: Pregnant women from 6 to 16 weeks of gestation require assessment for anemia and bone marrow response to plan support, counseling, and treatment for anemia during pregnancy.
Keywords: Pregnancy anemia; reticulocyte count